Challenges of Teaching Mathematics to Students With Visual Impairment - Oyebanji, M S; Idiong, Ubong Sam (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
This study aimed at investigating the challenges of teaching mathematics to visual impaired students in school of the blind, a case study of some selected schools for the visually impaired. Questionnaire and interview were used for data collection from the respondents. The hypotheses in the study were tested using t-test with Î±-level of 0.05 through SPSS. The study followed a cross-section survey design and involved 80 respondents 20 for the visually impaired students, 10 for the Mathematics teachers, 10 special mathematics teachers, 40 low vision and non-visually impaired students. The findings revealed the visually impaired students receive bursaries from the government and non-government organization; meal, accommodation, and few scholastic materials from their school; extra time during mathematics classes and examination and friend support. However, constraining limitations in the method of instruction assessment used and the instructional materials provided were noted, on the basis of these findings, recommendation towards the better education of the visually impaired student studying mathematics should be encouraged and employment of special mathematics teachers.